2011
DOI: 10.2217/pgs.10.174
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ABCB1 C3435T Polymorphism on Lymph node Regression in Multimodality Treatment of Locally Advanced Esophageal Cancer

Abstract: Our data supports the impact of ABCB1 on effectiveness of esophageal cancer treatment. SNPs of ABCB1 could be helpful in predicting lymph node regression in the multimodality treatment of locally advanced esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
1
14
1
Order By: Relevance
“…SNPs in ABC transporters can significantly change the activity. Narumiya et al have reported that SNP rs1045642 in ABCB1 (alias Pgp or MDR1, 171050) gene may affect the patient response to neoadjuvant chemoradiation, and, more specifically, the response of lymph node invaded by tumor cells [ 14 ].…”
Section: Search Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SNPs in ABC transporters can significantly change the activity. Narumiya et al have reported that SNP rs1045642 in ABCB1 (alias Pgp or MDR1, 171050) gene may affect the patient response to neoadjuvant chemoradiation, and, more specifically, the response of lymph node invaded by tumor cells [ 14 ].…”
Section: Search Results and Discussionmentioning
confidence: 99%
“…The rs2032582 SNP has recently been studied as a part of panel of five SNPs (single SNPs in genes ABCB1 , 5,10-Methylenetetrahydrofolate reductase ( MTHFR , 607093), Glutathione S -transferase, pi ( GSTP1 , 134660), and two SNPs in Xeroderma pigmentosum, complementation group C ( XPC , 613208) modifying progression-free survival of 124 locally advanced EC (62 with ESCC and 62 with EAC) patients who received neoadjuvant chemoradiation based on cisplatin, docetaxel, and 5-fluorouracil [ 18 ]. Although Okuno et al found no association of rs1045642 SNP with response rate or survival of ESCC patients [ 19 ], Narumiya et al have analyzed impact of ABCB1 rs1045642 SNP on outcome of EC patients (116 with ESCC and 146 with EAC) after neoadjuvant treatment with cisplatin- and 5-fluorouracil-based chemoradiation and observed that CC genotype was associated with lymph node and distant metastases and predicted shorter overall survival [ 14 ]. These differences could be due to different frequency of rs1045642 SNP in studied populations, Caucasian (Narumiya et al) [ 14 ] versus Japanese (Okuno et al) [ 19 ].…”
Section: Search Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that the increased risk of ESCC relates to combined SULT1A12*2 genotype and CYP3A5 heterozygous genotypes, especially in tobacco smokers (Dandara et al, 2006). SNP of ATP-binding cassette sub-family B (MDR/TAP) member 1 gene (ABCB1) was reported to be associated with lymph node and distant metastases in EC (Narumiya et al, 2011). SNP also impacted disease-free survival (DFS) of ECs.…”
Section: Effects Of Mutations and Snps In Esophageal Cancermentioning
confidence: 99%